Rethinking Platelet and Plasma Transfusion Strategies for Neonates: Evidence, Guidelines, and Unanswered Questions - Sokou, Rozeta; Gounari, Eleni A.; Lianou, Alexandra; Tsantes, Andreas G.; Piovani, Daniele; Bonovas, Stefanos; Iacovidou, Nicoletta; Tsantes, Argirios E. (Seminars in Thrombosis and Hemostasis, 2025)
The transfusion of platelets and fresh frozen plasma (FFP) to critically ill neonates in neonatal intensive care units (NICUs) is a common intervention, yet it is still widely performed without adhering to international guidelines. The guidance itself on the therapeutic management of neonatal coagulation disorders is generally limited due to the absence of strong indications for treatment and is mainly aimed at the prevention of major hemorrhagic events such as intraventricular hemorrhage (IVH) in premature neonates. Historically, the underrepresentation of neonates in clinical studies related to transfusion medicine had led to significant gaps in our knowledge regarding the best transfusion practices in this vulnerable group and to a wide variability in policies among different neonatal units, often based on local experience or guidance designed for older children or adults, and possibly increasing the risk of inappropriate or ineffective interventions. Platelet transfusion and, particularly, FFP administration have been linked to potentially fatal complications in neonates and thus any decision needs to be carefully balanced and requires a thorough consideration of multiple factors in the neonatal population. Despite recent advances toward more restrictive practices, platelet and FFP transfusions are still subject to wide variability in practices.This review examines the existing literature on platelet and FFP transfusions and on the management of massive hemorrhage in neonates, provides a summary of evidence-based guidelines on these topics, and highlights current developments and areas for ongoing and future research with the aim of improving clinical practices.
Keywords: neonates; platelet transfusion; plasma transfusion; coagulation disorders; bleeding events